Addiction among high school students: determination of nicotine, substance, game, and internet addiction levels. - Korkmaz Aslan, Tuba; Batı, Serap (Journal of Substance Use, 2025)
Aim: The aims of this study were to determine the levels of cigarette smoking, psychoactive substances, game, and internet addiction among high school students and to examine whether addictions show a significant difference according to some socio-demographic variables and the relationships between addiction types. Method: A total of 530 high school students studying in Turkey, agreed to participate in the study. Data were collected through face-to-face interviews using the Sociodemographic Questionnaire (which contains DSM-V categories of addictive substances), Fagerström Test for Nicotine Dependence (FTND), Game Addiction Scale (GAS), and Internet Addiction Test (IAT). Results: Approximately 1.9% of the respondents were smokers and 0.8% were inhalant users. Respondents scored 7.43 ± 2.88 on FTND, 13.92 ± 5.57 on the GAS, and 43.44 ± 18.80 on the IAT. Male respondents received a higher average score on the GAS than female respondents, and female respondents received a higher average score on the IAT than male respondents. As body mass index increased, a statistically significant, positive and moderate correlation was found between GAS scores and IAT scores. Conclusion: Addictions are becoming more and more widespread and measures, information, and research should be increased and young people should be educated about addictions.